2012
DOI: 10.1002/ptr.4872
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic Activities of the Extracts and Isolated Flavonoids of Euphorbia cuneata Vahl

Abstract: The total alcohol extracts of Euphorbia cuneata Vahl.(Euphorbiaceae) were screened for antiulcerogenic activity using an ethanol-induced ulcer model at doses of 125, 250 and 500 mg/kg. The extracts possessed antiulcerogenic activity in a dose-dependent manner. Four flavonoidal compounds were isolated and identified as naringenin, aromadendrin, apigenin and 4'-O-methoxy-luteolin-7-O-rhamnoglucoside, each demonstrating antiulcerogenic activity with curative ratios ranging from 75.78% to 88.23%. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
3
28
1
Order By: Relevance
“…4) isolated from Euphorbia cuneata, a folk medicine used for the treatment of gastric disorders, demonstrated antiulcerogenic action. 43) These results confirm the potential value of flavonoids from TMPs, both in …”
Section: Flavonoidssupporting
confidence: 76%
See 1 more Smart Citation
“…4) isolated from Euphorbia cuneata, a folk medicine used for the treatment of gastric disorders, demonstrated antiulcerogenic action. 43) These results confirm the potential value of flavonoids from TMPs, both in …”
Section: Flavonoidssupporting
confidence: 76%
“…5) with a rhamnoglucosyl moiety at C-3 exhibited much higher activity. 65) It is not surprising that SAR studies provide information (41)(42)(43)(44) showed that a prenyl group at C-4 plays an important role in the inhibitory activity. SAR studies on a new nitrocontaining tetrahydroprotoberberine (45) and five isoquinoline alkaloids (46)(47)(48)(49)(50) showed that nitro substituents at ring A improve anti-AchE activity.…”
Section: Sar Studies On the Pharmacological Activity Ofmentioning
confidence: 99%
“… Preparation of fungal extract : ▪ For in‐vitro studies : Stock solutions of the total extracts and compounds were prepared at a concentration of 20 mg/mL in DMSO (Sigma, UK) and diluted to appropriate concentrations prior to assays. ▪ For in‐vivo studies : The methanol extracts of each investigated fungi and isolated compounds were freshly prepared by suspension in sterile normal saline with the aid of few drops of tween 80)Djalma dos Santos et al ., ) Acute toxicity (LD 50 ) test :An acute toxicity test was carried out for the alcohol extracts of D. rostrata and E. tonpholium according to Turner, (1965). Groups of mice, each of six, were used for testing doses up to 5000 mg/kg (Soliman et al ., ; Awaad et al ., ). Sub‐chronic toxicity :…”
Section: Methodsmentioning
confidence: 99%
“…For instance, orally given aqueous extract of date fruit induced a 40% inhibition of ulcer index while ethanol extract caused a 55% inhibition in ethanol-induced gastric ulcer (Al-Qarawi et al, 2005). Likewise, 125mg of euphorbia cuneata Vahl.-extracted with chloroform or ethanol only induced a 30% inhibition while the same dose of ethyl acetate extract induced 58% inhibition in ulcerogenesis in an ethanol-induced gastric ulcer model (Awaad et al, 2013). Melanchauski et al (2013) reported that 100mg/kg of the methanolic extract of Ailanthus excels bark caused 56% inhibition of ulcerogenesis while the same dose of diethyl ether extract induced 83% inhibition, which was the same efficacy as conventional antiulcer agent, such as carbenoxolone.…”
Section: Efficacymentioning
confidence: 99%